Cadaveric Study of Male Lumbar Intervertebral Foramina Morphometry in Ile-Ife - Sunday E. C; Abiodun A. A; Komolafe O.A; Akpokonyan T.E; Adeyemi D.O; Ofusori D.A (Journal of Krishna Institute of Medical Sciences University, 2018)
Background: This study was designed to investigate the mean lumbar foramina height and length in male cadaveric specimens in Ile-Ife. Aim and Objectives: Two hundred and fifty intervertebral foramina derived from twenty-five male cadaveric specimens were analyzed, were studied. They were obtained from the Department of Anatomy, Obafemi Awolowo University, Ile-Ife, Osun State in Southwestern Nigeria. The cadavers were positioned prone and a routine paraspinal approach was employed to gain exposure to the posterior spinal element following meticulous soft tissue dissection. An osteotomy of the iliac crest was performed to adequately expose the fifth lumbar (L1-S1) foramina.Parameters assessed were; the foramen height and the foraminal length. The measurement was performed three times on each side using vernier calipers. The variations of the different measurements in the cephalo-caudal direction were analyzed for statistical differences using the “One way ANOVA” with post hoc test. Results: The result showed a gradual increase of the foramina height were observed on both right and left side from L1-L2 to L3- L4 and from then on decreased progressively towards the L5-S1 level. No statistical difference was noted in the measurements derived (p<0.05). Conclusion: A good understanding of the lumbar intervertebral foraminal are essential in surgical planning of suitably sized cannulas necessary for less invasive spine surgeries as well as help in diagnosis of pathologies surrounding this important region following adequate clinical evaluation and measurements using imaging.